Product whole life-cycle and omni-channels data convergence oriented enterprise networks integration in a sensing environment - Li, Qing; Luo, Hao; Xie, Pei-Xuan; Feng, Xiao-Qian; Du, Rui-Yang (Computers in industry, 2015)
•New challenges of enterprise network integration in sensing environment are illustrated.•A data convergence oriented enterprise networks integration architecture with relative enabling technologies is developed in the paper.•Data Portal (DP) and Collaboration Agent (CA) concepts are introduced for data collection, transfer and fusion from different data sources.•Cases to solve problems of product lifecycle management and omni-channel marketing management are discussed. With the process of globalisation and the development of management models and information technologies, enterprise cooperation and collaboration meets a new business and technical environment. The Internet of things, mobile Internet, cloud computing and big data technologies build a sensing environment for all kinds of businesses. Inter enterprise collaboration is also meeting the new challenges of omni-channel marketing, closed-loop supply chain and enterprise networks integration. A data convergence oriented enterprise networks integration architecture with relative enabling technologies is developed in the paper. In order to collect, transfer and fuse data from different data sources, Data Portal (DP) and Collaboration Agent (CA) concepts are introduced, which present a lightweight and loosely coupled infrastructure for enterprise networks integration. How to use the developed technologies to solve problems of product lifecycle management and omni-channel marketing management are discussed in detailed cases studies.